2022
DOI: 10.3390/microorganisms10051045
|View full text |Cite
|
Sign up to set email alerts
|

Trust Your Gut: The Association of Gut Microbiota and Liver Disease

Abstract: The gut microbiota composition is important for nutrient metabolism, mucosal barrier function, immunomodulation, and defense against pathogens. Alterations in the gut microbiome can disturb the gut ecosystem. These changes may lead to the loss of beneficial bacteria or an increase in potentially pathogenic bacteria. Furthermore, these have been shown to contribute to the pathophysiology of gastrointestinal and extra-intestinal diseases. Pathologies of the liver, such as non-alcoholic liver disease, alcoholic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 159 publications
(232 reference statements)
1
24
0
1
Order By: Relevance
“…Intestinal microbiome disorders may also affect the progression of liver fibrosis. In patients with chronic liver disease, bacteria and their products are often transported across the intestinal barrier that has been disrupted [ 171 ]. Blocking Toll-like receptor 4 (TLR4) signaling in mice and reducing liver exposure to intestinal microbes by using antibiotics decelerate the development of liver fibrosis [ 172 ].…”
Section: Fibrotic Diseases: Pathogenesis and Mechanismmentioning
confidence: 99%
“…Intestinal microbiome disorders may also affect the progression of liver fibrosis. In patients with chronic liver disease, bacteria and their products are often transported across the intestinal barrier that has been disrupted [ 171 ]. Blocking Toll-like receptor 4 (TLR4) signaling in mice and reducing liver exposure to intestinal microbes by using antibiotics decelerate the development of liver fibrosis [ 172 ].…”
Section: Fibrotic Diseases: Pathogenesis and Mechanismmentioning
confidence: 99%
“…Hepatitis B virus (HBV) infection, Hepatitis C virus (HCV) infection, alcohol abuse and nonalcoholic fatty liver disease (NAFLD) is currently the most common cause of chronic hepatitis and HCC worldwide (17, 18). Some studies have found that the gut microbiota has significant influence in the development of liver cirrhosis, liver ischemic injury, NAFLD, HCC, and liver graft rejection (19)(20)(21)(22). Additionally, the gut microbiotas of HCC patients are significantly different from those of normal subjects, and changes in the composition of gut microbiotas could reveal to grade severity or progression of illness in HCC (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…These include steatosis, inflammation, and liver damage. Liver disorders such as primary cholangitis or spotted liver disease in poultry farming can be caused by both qualitative and quantitative changes in the gut microbiota [ 72 , 73 ]. A healthy liver is a barrier between systemic circulation and the intestines.…”
Section: Gut-liver Axismentioning
confidence: 99%